Relationships between Institutional Capital, Dynamic Capabilities and Competitive Advantage: Empirical Examination of the Agribusiness Sector - Vilani Sachitra; Siong-Choy Chong (International Review of Management and Marketing, 2017)
Resource-based view (RBV) is based on the economic rent concept which explains sources of competitive advantage at firm level. The RBV lacks a causality chain between resources and competitive advantage which calls for further examination along with dynamic capabilities possessed by firms. This study aims to determine the relationship between institutional capital, dynamic capabilities and competitive advantage of agribusiness firms, more specifically the minor export crop farms, at the same time contending that the relationship between institutional capital and competitive advantage is mediated by the specific capabilities. The scope of the study comprises entities which have experience in commercial cultivation of minor export crops. 456 farm owners were selected from the highest growing districts of the selected crops (cinnamon, clove and pepper) using proportionate stratified random sampling technique. Self-administratedstructured questionnairewas used to collect data. The regression-based path analysis was used to measure the direct and mediation relationship amongst the latent variables. The results of the study suggest that institutional capital has a significant influence on both the quality management capability and marketing capability. This connection contributes valuable insights to the empirical support on the importance of specific capabilities on sustainable competitive advantage. Managerial implications are highlighted along with future research directions.